Agricultural productivity, inter-sectoral labor shift, and economic growth in India - Balaji, S. J.; Babu, Suresh Chandra (International Food Policy Research Institute, 2020)
In this paper, we study the transformation process Indian agriculture exhibited in the recent past, studying its policy implications. Between the years 2005-06 and 2015-16, more than 52 million workers left agriculture, which did not have any effect on agricultural output due to productivity improvements. We estimate the contribution of productivity growth and structural change in agriculture to national productivity growth during 1981-2016. We estimate differentials in agricultural productivity and in their ability to contribute to the structural change process for 21 major states of India. Using revised employment estimates, we trace major changes during the pre-reforms (before 1991) and post-reforms periods. Results show that in the pre-reforms period, the impact of productivity improvements in agriculture on agricultural output was equated by the new workforce entering into this sector, leading to a stagnant labor productivity trend. The labor-shift from agriculture during the early years of the post-reforms period, which increased further in the next decade, has led to a consistent rise in agricultural productivity. In the absence of reforms and the associated labor shift, the productivity growth in Indian agriculture would have been much lower. A similar labor shift during the last decade has not affected agricultural output, which has risen more rapidly. This result holds true for almost all states studied. There exists a positive relation between labor-shift and agricultural output in a cluster of states. Decomposition results indicate ‘within-sector’ productivity growth is the major source of overall growth, with a rising contribution of ‘structural change’. Studying the sources of growth across states offers new scope to achieve inter-sectoral productivity convergence.